Melatonin Inhibits Oxidative Stress and Apoptosis in Cryopreserved Ovarian Tissues via Nrf2/HO-1 Signaling Pathway - Sun, Tie Cheng; Liu, Xiao Chao; Yang, Song He; Song, Ling Li; Zhou, Shan Jie; Deng, Shou Long; Tian, Li; Cheng, Lu Yang (Frontiers in Molecular Biosciences, 2020)
Female fertility preservation is a major area of interest within the field of assisted reproductive technology, in particular the ovarian tissue cryopreservation of adolescent cancer patients. Melatonin (MLT) has been instrumental in our understanding of anti-oxidative and anti-apoptotic properties. Whether melatonin (MLT) can ameliorate the cryoinjury and the generation of reactive oxygen species (ROS) in cryopreserved ovarian tissues (OTs) has never been investigated. Here, we demonstrated that MLT protects follicular intact, follicular diameter and cells apoptosis in cryopreserved rat ovarian tissues (OTs). Additionally, MLT decreased reactive oxygen species (ROS) level, increased glutathione peroxidases (GSH-Px), glutathione (GSH), catalase (CAT), superoxide dismutase (SOD) activities, decreased malondialdehyde (MDA) and nitric oxide (NO) activities in cryopreserved OTs. Interestingly, this correlation is related to the activation of the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway and promoted the expressions of anti-oxidative mRNAs including heme oxygenase-1 (HO-1), glutathione S-transferase M1 (GSTM1), superoxide dismutase (SOD) and catalase (CAT). In summary, MLT not only directly scavenges ROS, but also significantly induces the activation of anti-oxidative enzymes via Nrf2 signaling pathway, revealing a new mechanism of action that supports the protection of anti-oxidative stress in cryopreserved OTs.